La fotografía y el herbario como formas de representación en los derrotados de Pablo Montoya - Cimadevilla, Pilar María (2017)
The aim of this article is to analyze in first place the way in which photography is inserted into Los Derrotados, by means of both an explicit reference to photographic images as well as a theoretical reflection on the scope of this technical medium. Secondly, we are interested in studying the role of the herbarium as one of the devices which, before the invention of photography, has revealed the major problem of representation across theoretical studies on image since the 19th century up to date. Finally, we are going to explore the ties among the image, the herbarium and the biographical genre.